Predictive ability of cardiopulmonary exercise test parameters in heart failure patients with cardiac resynchronization therapy. (14th October 2021) - Dias Ferreira Reis, J.P; Goncalves, A; Bras, P; Moreira, R; Rio, P; Pereira Silva, T; Timoteo, A; Soares, R; Cruz Ferreira, R
Abstract: Introduction: There is evidence suggesting that a peak oxygen uptake (pVO2) cut-off of 10ml/kg/min provides a more precise risk stratification in Cardiac Resynchronization Therapy (CRT) patients. Our aim was to compare the prognostic power of several cardiopulmonary exercise testing (CPET) parameters in patients with CRT and assess the discriminative ability of the guideline-recommended pVO2 cut-off values. Methods: Prospective evaluation of consecutive heart failure (HF) patients with left ventricular ejection fraction ≤40%. The primary endpoint was a composite of cardiac death and urgent heart transplantation (HT) in the first 24 follow-up months and was analyzed by several CPET parameters for the highest area under thecurve (AUC) in the CRT group. A survival analysis was performed to evaluate the risk stratification provided by several different cut-offs. Results: A total of 450 HF patients, of which 114 had a CRT device. These patients had a higher baseline risk profile, but there was no difference regarding the primary outcome (13.2% vs 11.6%, p=0.660). End-tidal carbon dioxide pressure at the anaerobic threshold (PETCO2AT) had the highest AUC value, which was significantly higher than that of pVO2 in the CRT group (0.951 vs 0.778, p=0.046). The currently recommended pVO2 cut-off provided accurate risk stratification in this setting (p<0.001), and the suggested cut-off value of 10 ml/min/kg did not improve risk discrimination in device patients (p=0.772). Conclusion: PETCO2AT outperforms pVO2's prognostic power for adverse events in CRT patients. The current guideline-recommended pVO2 cut-off can precisely risk-stratify this population. Funding Acknowledgement: Type of funding sources: None.